Implementation of Home-based Experiment on Photosynthesis Material to Improve Students’ Science Process Skill - D. Desmiawati; I. Kaniawati; S. Anggraeni; N. S. Putra (Universitas Negeri Yogyakarta, 2023)
This study aimed to describe the improvement of students' science process skills (SPS) after the implementation of home-based experiment activities on photosynthesis material. This research was carried out at one of the State Junior High Schools in Garut. The sample was 26 students for the experimental classes and 25 students for the control class. The research design was Pre-Posttest Control Group Design. The sample selection technique used the convenience sampling technique. The success of the learning method/model implemented was assessed through value analysis before (pretest) and after (posttest) given treatment in the experimental and control groups. The N-Gain value of the experimental group was 0.678, while the N-Gain value of the control group was 0.52. This indicated that the N-gain value of the experimental group was higher than the control group. But, the statistical analysis using post-test scores showed that there was no significant difference between the experimental group and the control group in the students’ SPS. So, the implementation of home-based experiments and ordinary practicum in the learning process has the same effect on students’ SPS results. Therefore, home-based experiments should be an option for teachers in science learning because, even though the learning process is online, the practicum is the identity, and support of science learning should not be eliminated.